Negative current collector, negative pole piece and lithium ion battery
By introducing inorganic particles into the negative electrode current collector conductive layer of the lithium-ion battery, the roughness of the conductive layer surface is improved, and the problem of defiling the active material layer during the circulation process is solved, thereby achieving higher peeling force and cycle stability.
Patent Information
- Application Number
- CN202411846737.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The negative electrode sheets of existing lithium-ion batteries are prone to defiling of the negative electrode active material layer during the cycle, resulting in deterioration of the battery cell performance and insufficient peeling force are the main problems.
By introducing inorganic particles into the conductive layer of the negative electrode current collector, the roughness of the surface of the conductive layer is increased, thereby increasing the degree of mechanical engagement between the negative electrode active material layer and the negative electrode current collector, reducing slippage during rolling, and improving peeling force.
It effectively reduces the risk of active material falling off during the negative electrode circulation, improves the peeling force of the negative electrode active material layer, and improves the cycle stability and performance of the battery.
Smart Images

Figure CN119674085A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode current collector, a negative electrode plate and a lithium ion battery. Background Art
[0002] With the development of lithium-ion batteries, high-capacity batteries have become a hot topic in current research. Adding silicon to graphite anode is an effective means to increase battery capacity. However, the expansion of silicon anode is as high as 300-400%, so the addition of silicon causes the electrode to expand severely during the cycle.
[0003] At present, the negative electrode plates of lithium-ion batteries are generally made by directly coating the negative electrode slurry on a bare copper foil (negative electrode current collector) to form a negative electrode active material layer. However, the surface of the bare copper foil is relatively smooth and the bonding strength with the negative electrode slurry is relatively weak. During the production process and subsequent battery cycles, as the plate expands and internal stress is released, the negative electrode active material layer is prone to peeling off, deteriorating the performance of the battery cell.
[0004] Therefore, improving the peeling force between the negative electrode active material layer and the negative electrode current collector is crucial to the development of high-capacity batteries. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a negative electrode current collector and a lithium ion battery to improve the problem of insufficient peeling force between the negative electrode current collector and the negative electrode active material layer.
[0006] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a negative electrode current collector, which includes: a current collector substrate and a conductive layer, and the conductive layer is arranged on the current collector substrate; wherein, based on the total weight of the conductive layer as 100%, the conductive layer includes the following components: 55-60% conductive agent, 35-37% binder and 3-10% inorganic particles; the inorganic particles partially protrude from the surface of the conductive layer, and the size of the inorganic particles protruding from the surface of the conductive layer is 0.1μm to 0.2μm.
[0007] In one embodiment of the present invention, the conductive agent includes a first conductive agent, and the first conductive agent includes conductive graphite.
[0008] In one embodiment of the present invention, the particle size D50 of the conductive graphite is 0.7 μm to 1 μm.
[0009] In one embodiment of the present invention, the conductive agent further includes a second conductive agent, and the second conductive agent includes one or more of Ketjen black, carbon nanotubes, graphene, and carbon fibers.
[0010] In one embodiment of the present invention, the mass ratio of the first conductive agent to the second conductive agent is (3-5):1.
[0011] In one embodiment of the present invention, the single-side thickness of the conductive layer is 0.7 μm to 1 μm.
[0012] In one embodiment of the present invention, the particle size D10 of the inorganic particles is 0.8 μm to 1 μm, and D95 is 0.9 μm to 1.2 μm.
[0013] In one embodiment of the present invention, the inorganic particles include one or both of boehmite and alumina; and / or the binder is one or more of modified polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, and polymethyl methacrylate.
[0014] Another aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising any one of the above-mentioned negative electrode current collectors and a negative electrode active material layer located on the conductive layer of the negative electrode current collector.
[0015] In one embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material.
[0016] The present invention also provides a lithium ion battery, which comprises the negative electrode sheet described above in the present invention.
[0017] The negative electrode current collector of the present invention is provided with a conductive layer on the current collector substrate, and inorganic particles are introduced into the conductive layer to increase the roughness of the conductive layer surface, thereby increasing the degree of mechanical engagement between the negative electrode active material layer and the negative electrode current collector, reducing slippage during rolling, and improving the peeling force of the negative electrode active material layer, thereby reducing the risk of active material falling off during the negative electrode cycle.
[0018] Furthermore, the type of conductive agent in the conductive layer is adjusted, and large-particle conductive graphite is compounded with small-particle second conductive agent. The small-particle second conductive agent is filled between the graphite pores to increase the contact area between the negative electrode material and the conductive layer and reduce the internal resistance of the electrode. At the same time, the conductive agent compounded with large and small particles can build a complex pore structure, so that the embedding effect of the negative electrode active material layer is better, it is easier to hinder the interface slip, further improve the stripping force of the negative electrode active material layer, and reduce the glue consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0020] Figure 1A schematic diagram of the structure of a negative electrode current collector in one embodiment of the present invention;
[0021] Figure 2 FIG. 1 is a schematic structural diagram of a negative electrode plate in one embodiment of the present invention.
[0022] Reference numerals:
[0023] 10. Negative electrode current collector; 11. Current collector matrix; 12. Conductive layer; 100. Negative electrode plate; 101. Negative electrode active material layer. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are to describe specific specific embodiments, rather than to limit the scope of protection of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints of the numerical range (i.e., the minimum value and the maximum value), as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe a feature or characteristic, these numerical ranges can be combined.
[0027] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0028] In this article, D50: also known as median diameter or median particle size, refers to the particle size value corresponding to the cumulative distribution number percentage reaching 50%. This means that 50% of the particles have a particle size smaller than this value, and 50% of the particles have a particle size larger than this value. D50 is often used to indicate the average particle size of a powder and is an important indicator for measuring the particle size of a powder.
[0029] D10: indicates the particle size value when the cumulative distribution number percentage reaches 10%. This means that 10% of the particles are smaller than this value and 90% are larger than this value. D10 is usually used to characterize the fine particle part in the powder.
[0030] D95: indicates the particle size value corresponding to the cumulative distribution number percentage reaching 95%. This means that 95% of the particles have a particle size smaller than this value and 5% of the particles have a particle size larger than this value. D95 is usually used to characterize the coarse particle portion in a powder.
[0031] The negative electrode plate is a negative electrode active material layer coated on the negative electrode current collector, and the expansion of the negative electrode will cause the negative electrode active material layer to fall off from the negative electrode current collector. In order to reduce the shedding of active materials caused by the expansion of silicon negative electrodes, the industry introduced carbon-coated copper foil with reference to the idea of carbon-coated aluminum foil. The purpose is to increase the contact area between the negative electrode active material and the copper foil and improve the peeling force between it and the current collector. The surface roughness of conventional carbon-coated copper foil is small, and it is difficult for negative electrode particles to embed into the pores of the coating, resulting in poor mechanical meshing between the negative electrode active material layer and the coating. Slippage is prone to occur when the plate is rolled, which makes the peeling force of the negative electrode active material layer worse, even worse than that of bare copper foil.
[0032] Based on this, the present invention provides a negative electrode current collector, a negative electrode pole piece including the negative electrode current collector, and a lithium ion battery including the negative electrode pole piece. Inorganic particles are introduced into the conductive layer of the negative electrode current collector, and the inorganic particles are partially protruded from the surface of the conductive layer to increase the roughness of the conductive layer surface, thereby increasing the degree of mechanical engagement between the negative electrode active material layer and the negative electrode current collector, reducing slippage during rolling, and improving the peeling force of the negative electrode active material layer, thereby reducing the risk of active material falling off during negative electrode cycling.
[0033] See also Figure 1 In the first aspect of the present invention, a negative electrode current collector is provided, and the negative electrode current collector 10 includes a current collector matrix 11 and a conductive layer 12. Among them, the current collector matrix 11 adopts a current collector material conventional in the art suitable for the negative electrode of the battery, such as copper foil (plain foil, no other materials coated on the surface); the conductive layer 12 is arranged on the current collector matrix 11, and the conductive layer 12 can reduce the contact resistance between the negative electrode active material layer and the negative electrode current collector 10, improve the peeling force between the negative electrode active material layer and the negative electrode current collector 10, and improve the shedding problem of the negative electrode active material layer. The current collector matrix 11 has a first surface and a second surface arranged oppositely. The conductive layer 12 can be arranged on the first surface or the second surface of the current collector matrix 11, and can also be arranged on the first surface and the second surface at the same time, which is selected according to the design requirements of the battery.
[0034] The conductive layer 12 in the present invention includes a conductive agent, a binder and inorganic particles, wherein the conductive agent is used to improve the conductivity and reduce the internal resistance of the pole piece, the binder is used to bond the conductive agent and the inorganic particles, and bond the conductive agent and the inorganic particles to the current collector matrix 11, the inorganic particles have a certain hardness, and the degree of deformation is small during the rolling process of the pole piece, and the addition of inorganic particles to the conductive layer 12 can increase the roughness of the surface of the conductive layer 12, and realize the mechanical engagement between the negative electrode active material layer and the conductive layer 12. Taking the total weight of the conductive layer 12 as 100%, the conductive agent in the conductive layer 12 is 55% to 60%, such as 55%, 58% or 60%, etc., the binder is 35% to 37%, such as 35%, 36% or 37%, etc., and the inorganic particles are 3% to 10%, such as 3%, 5%, 8% or 10%, etc. When the ratio of each substance in the conductive layer 12 is within the above range, it can improve the conductivity of the electrode sheet and the degree of mechanical meshing between the negative electrode active material layer and the negative electrode current collector 10, thereby improving the peeling force of the negative electrode active material layer. If it exceeds the above range, it will affect the battery performance. For example, if the content of the binder and inorganic particles is too high, the content of the conductive agent will be reduced accordingly, which will increase the electrode sheet resistance and affect the electrical performance of the battery; if the content of inorganic particles is too low, the roughness of the conductive layer 12 will not change significantly, and the mechanical meshing between the negative electrode active material layer and the conductive layer 12 cannot be achieved; if the content of the binder is too low, the bonding effect between the conductive agent and the inorganic particles and the bonding effect between the conductive layer 12 and the current collector matrix 11 are weak, which affects the peeling force between the conductive layer 12 and the current collector matrix 11, and further affects the peeling force of the negative electrode active material layer.
[0035] In one embodiment, the conductive agent includes a first conductive agent, and the first conductive agent includes conductive graphite. The conductive graphite has good adhesion to the current collector matrix 11, and can effectively improve the bonding strength between the negative electrode active material layer and the current collector matrix 11, thereby avoiding the problem of negative electrode shedding during the production process and subsequent battery cycles as the pole piece expands and the internal stress is released. The particles of the conductive graphite are approximately spherical, and the particle size D50 is 0.7μm to 1μm, such as 0.7μm, 0.8μm, 0.9μm or 1μm.
[0036] Furthermore, the conductive agent also includes a second conductive agent, and the addition of the second conductive agent can further improve the conductivity of the pole piece. The second conductive agent includes but is not limited to Ketjen black (KB), carbon nanotubes (CNTs), graphene, and carbon fiber (VGCF). The second conductive agent can be selected from any one of the materials listed above, or any combination of two or more. For example, the second additive is Ketjen black, or a combination of Ketjen black and carbon nanotubes, or a combination of graphene, carbon fiber and carbon nanotubes. When the second conductive agent is selected from a combination of two or more, there is no restriction on the ratio between the components in the composition, and any proportion can be mixed. The particle size of the second conductive agent is smaller than the particle size of the conductive graphite. The large-particle conductive graphite and the small-particle second conductive agent are more likely to build the pore structure in the conductive layer 12, increase the contact area between the negative electrode active material and the negative electrode current collector 10, and reduce the internal resistance of the pole piece. At the same time, the rich pore structure in the conductive layer 12 makes the embedding effect of the negative electrode active material layer better, and it is easier to hinder the interface slip, and further improve the peeling force of the negative electrode active material layer. In some embodiments, the mass ratio of the first conductive agent to the second conductive agent is (3-5):1, for example, 3:1, 4:1 or 5:1, etc. Since the conductivity of the second conductive agent is better than that of the first conductive agent, the higher the proportion of the second conductive agent, the better the conductivity of the electrode sheet, but since the particle size of the second conductive agent is smaller than that of conductive graphite and the specific surface area is larger, when the proportion of the second conductive agent is too high, more glue will be consumed, resulting in insufficient peeling force between the conductive layer 12 and the current collector matrix 11.
[0037] The binder can be a conventional binder in the art. In some embodiments, the binder can be one or more of modified polyacrylic acid (PAA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polymethyl methacrylate (PMMA). The binder can be a single material, such as modified polyacrylic acid; the binder can also be a combination of two or more, such as a combination of styrene-butadiene rubber and carboxymethyl cellulose. It should be noted that the above-mentioned modified polyacrylic acid can be chemically modified by hydrophobic groups such as ester groups and amide groups, or it can be a blended modification mixed with polyvinyl alcohol, but is not limited to this. The use of modified polyacrylic acid can improve the water resistance of the conductive layer 12 and prevent the aqueous slurry of the negative electrode from damaging the conductive layer 12.
[0038] The inorganic particles are selected from inorganic materials with a certain hardness and the material is compatible with the electrochemical system of the battery to prevent the electrochemical balance of the battery from being destroyed. In some embodiments, the inorganic particles include but are not limited to boehmite and alumina. The inorganic particles can be a single material, such as boehmite or alumina; the inorganic particles can also be a combination of two or more materials, such as a combination of boehmite and alumina. Furthermore, the inorganic particles are selected from alumina, which has a higher hardness than boehmite. During the rolling process of the pole piece, the deformation of alumina is smaller, and it is easier to hinder the slip of the negative electrode material at the interface.
[0039] In the present invention, the size of the inorganic particles protruding from the surface of the conductive layer 12 is 0.1 μm to 0.2 μm, such as 0.1 μm, 0.15 μm or 0.2 μm. If the size of the inorganic particles protruding from the surface of the conductive layer 12 is less than 0.1 μm, the roughness of the surface of the negative electrode current collector 10 cannot be effectively increased; if the size of the inorganic particles protruding from the surface of the conductive layer 12 is too large, the overall thickness of the conductive layer 12 will be affected, and the electrode sheet will also be damaged.
[0040] The size of the inorganic particles protruding from the surface of the conductive layer 12 is jointly determined by the coating thickness of the conductive layer 12 and the particle size of the inorganic particles. In some embodiments, the single-sided coating thickness of the conductive layer 12 is less than or equal to 1 μm, further, the single-sided coating thickness of the conductive layer 12 is 0.7 μm to 1 μm, and further, the single-sided coating thickness of the conductive layer 12 is 0.8 μm. The particle size of the inorganic particles must ensure that part of the pole piece protrudes from the surface of the conductive layer 12 after rolling to increase the surface roughness of the conductive layer 12. In some embodiments, the particle size D10 of the inorganic particles is 0.8 μm to 1 μm, such as 0.8 μm, 0.9 μm or 1 μm, and D95 is 0.9 μm to 1.2 μm, such as 0.9 μm, 0.95 μm, 1.0 μm, 1.05 μm or 1.2 μm, etc. The appearance of boehmite or alumina is spherical. When the particle size satisfies D10 of 0.8 μm to 1 μm and D95 of 0.9 μm to 1.2 μm, the size of the inorganic particles protruding from the surface of the conductive layer 12 can be 0.1 μm to 0.2 μm.
[0041] The negative electrode current collector of the present invention introduces inorganic particles with a certain hardness into its conductive layer, and by adjusting the thickness of the conductive layer and the particle size of the inorganic particles, the inorganic particles are partially protruded from the surface of the conductive layer, thereby increasing the surface roughness of the conductive layer, increasing the degree of mechanical engagement between the negative electrode active material layer and the negative electrode current collector, reducing the slippage of the negative electrode active material layer during the rolling process of the pole piece, improving the stripping force of the negative electrode active material layer, and reducing the risk of the negative electrode active material falling off during the cycle. In addition, by adjusting the ratio of the conductive agent, the binder and the inorganic particles in the conductive layer, the conductivity is improved while the stripping force of the negative electrode active material layer is improved, and the pole piece resistance is reduced.
[0042] The present invention also provides a method for preparing the negative electrode current collector 10, which comprises the following steps:
[0043] 1) Dry-mix the conductive agent, the binder and the inorganic particles in proportion to ensure that the conductive agent, the binder and the inorganic particles are fully mixed; the dry-mixing method is not limited here, and the conventional mixing method in the art can be used, such as mixing and stirring with a planetary mixer. In this step, the mass ratio of the conductive agent, the binder and the inorganic particles is (55-60%): (35-37%): (3-10%).
[0044] 2) Add deionized water to the dry powder mixture of step 1) in batches for high-speed dispersion to obtain a uniformly dispersed conductive paste. In this step, the solid content of the conductive paste is 8±2%, and the viscosity of the conductive paste is 20 to 60 mpa.s, for example, 20 mpa.s or 40 mpa.s or 60 mpa.s.
[0045] Furthermore, solvents such as isopropyl alcohol may be added to the conductive paste as needed to reduce the surface tension of the paste, allowing it to better wet and level on the surface of the current collector substrate to prevent coating leaks.
[0046] Conductive slurry viscosity test method: using the American BROOKFIELD DV2T viscometer, using a No. 62 rotor, a speed of 30 rpm for testing, and the test time is 1 minute and 30 seconds.
[0047] Conductive paste solid content test method: Use Japan Shimadzu solid content tester MOC-120H to bake the sample at 120°C. When the weight change is less than 0.01% within 5 seconds, the measurement is completed and the reading is taken.
[0048] 3) The conductive slurry prepared in step 2) is coated on the current collector substrate 11 , and then dried and rolled up to obtain the negative electrode current collector 10 .
[0049] The conductive paste can be coated by any method in the art that can evenly coat the conductive paste, such as coating the conductive paste on the current collector substrate 11 by gravure transfer coating, with the coating surface density controlled at 0.4 to 0.8 g / m 2 , for example 0.4g / m 2 , 0.6g / m 2 or 0.8g / m 2 wait.
[0050] See also Figure 2, the second aspect of the present invention provides a negative electrode sheet 100, which includes a negative electrode current collector 10 and a negative electrode active material layer 101. Among them, the negative electrode current collector 10 is the negative electrode current collector 10 described above in the present invention, and the negative electrode active material layer 101 is disposed on the conductive layer 12 of the negative electrode current collector 10.
[0051] The negative electrode active material layer 101 includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. Among them, the negative electrode active material is selected from materials capable of intercalating and deintercalating lithium ions. Specifically, the negative electrode active material can be selected from graphite-based negative electrode materials and / or silicon-based negative electrode materials. Graphite-based negative electrode materials include, but are not limited to, natural graphite, artificial graphite, soft carbon, hard carbon, etc.; silicon-based negative electrode materials include silicon oxides SiOx (0 < x < 2), silicon-carbon materials, silicon单质, etc. However, the present application is not limited to these materials listed above, and other conventional materials that can be used as negative electrode active materials can also be used. These negative electrode active materials can be used alone or in combination of two or more. The negative electrode conductive agent can improve the electronic conductivity and play a role in collecting microcurrents between the negative electrode active materials and between the negative electrode active material and the negative electrode current collector 10 to reduce the contact resistance of the battery and accelerate the electron movement rate. In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotube, graphene. Optionally, the negative electrode conductive agent is conductive carbon black; or, a composition of carbon fiber and conductive carbon black; or, a composition of carbon nanotube and graphene, etc. The binder is used to bond the negative electrode active material and the negative electrode conductive agent and provide a certain adhesive force for the negative electrode active material layer 101 to bond it to the negative electrode current collector 10. As an example, the negative electrode binder is selected from at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), styrene-acrylate, acrylic acid-based multi-component copolymer. For example, the negative electrode binder is polyvinylidene fluoride, or a composition of styrene-butadiene rubber and carboxymethyl cellulose, etc. The ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder can refer to the conventional settings in the art.
[0052] The negative electrode sheet 100 can be prepared by a conventional preparation method in the art. As an example: First, the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder are mixed and stirred evenly in a solvent such as deionized water according to a certain ratio to form a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode current collector 10, and after processes such as drying, winding, and rolling, the negative electrode sheet is obtained.
[0053] Due to the increased surface roughness of the conductive layer of the negative electrode current collector of the negative electrode sheet of the present invention, the mechanical meshing degree between the negative electrode active material layer and the conductive layer is increased, the slippage of the negative electrode active material during the rolling process is reduced, the peel strength of the sheet is increased, and thus the risk of the negative electrode active material falling off during the cycle is reduced.
[0054] A third aspect of the present invention provides a lithium-ion battery, which includes the negative electrode plate 100 or the negative electrode current collector 10 of the present invention.
[0055] The lithium ion battery of the present invention can be a liquid battery or a solid battery. The composition of the lithium ion battery is described in detail below by taking the lithium ion battery as a liquid battery as an example.
[0056] The liquid lithium-ion battery includes not only the negative electrode plate 100 , but also a positive electrode plate, a separator and an electrolyte.
[0057] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector may be made of conventional materials in the art, such as aluminum foil, carbon-coated aluminum foil, etc. The positive electrode active material layer may be disposed on the surface of one side of the positive electrode current collector, or on the surface of both sides. The positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, wherein the positive electrode active material may be selected from any positive electrode material suitable for lithium-ion batteries, that is, compounds that can reversibly embed and deintercalate lithium ions may be used. As an example, the positive electrode active material may be a ternary material, such as a nickel-cobalt-manganese ternary material (NCM), a nickel-cobalt-aluminum ternary material (NCA), etc., and the iron-lithium positive electrode material may be, for example, lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), etc., and may also be a traditional material such as lithium cobalt oxide, lithium manganese oxide, etc. These materials may be used alone or in combination. The positive electrode binder is, for example, any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene-butadiene rubber (SBR), etc. The positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotubes, and graphene. Optionally, the conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotubes and graphene, etc. The ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can refer to the conventional settings in the art.
[0058] The positive electrode sheet can be prepared by conventional preparation methods in the art. For example, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder are first mixed and stirred in a solvent such as N-methylpyrrolidone (NMP) according to a certain ratio to form a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, a positive electrode sheet is obtained.
[0059] The diaphragm is set between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode to prevent short circuit inside the battery, and at the same time allow lithium ions to pass through and move between the positive and negative electrodes to realize the battery's charge and discharge process. The diaphragm can be made of porous materials such as polyethylene film (PE), polypropylene film (PP), glass fiber film or composite film. The thickness of the diaphragm is 9 to 18μm, the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%.
[0060] The electrolyte plays a role in conducting lithium ions during the charge and discharge process of the battery. In some embodiments, the electrolyte includes an organic solvent and a lithium salt, and the lithium salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). Further, the lithium salt is selected from lithium hexafluorophosphate with better comprehensive performance or a combination of lithium hexafluorophosphate and other lithium salts, such as a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The organic solvent may be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC). The electrolyte may also include functional additives such as fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), vinylene carbonate (VC), and diethylene sulfate (DTD), which may be added according to actual production needs.
[0061] Battery assembly: Place the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to isolate them, and obtain a bare cell by winding or stacking. Put the bare cell into the battery shell, and obtain a lithium-ion battery after assembly, injection, formation, and capacity division.
[0062] It should be noted that the structures not described in detail in the above lithium-ion battery can be configured with reference to the prior art and will not be described in detail here.
[0063] The lithium-ion battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0064] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0065] Example 1
[0066] This embodiment provides a negative electrode current collector, which includes a current collector matrix and a conductive layer disposed on the current collector matrix, wherein the current collector matrix is copper foil, the conductive layer includes a conductive agent, a binder and inorganic particles, the conductive agent is conductive graphite, the particle size D50 is 0.8 μm, the binder is SBR and CMC, and the mass ratio of the two is 1:1.33, the inorganic particles are boehmite, the particle size D10 of boehmite is 0.9 μm, and D95 is 0.98 μm; the mass ratio of the conductive agent, the binder and the inorganic particles is 58:36:6. The thickness of the conductive layer is 0.8 μm, and the size of the boehmite protruding from the conductive layer is 0.15 μm, which is measured by a white light interferometer, and the specific parameters are shown in Table 1.
[0067] The preparation process of the negative electrode current collector in this embodiment is as follows:
[0068] The conductive slurry was prepared according to the mass ratio of conductive graphite, binder (SBR+CMC) and boehmite of 58:36:6; during the preparation, the conductive graphite and boehmite were first fully dry-mixed, and then the binder SBR+CMC was added in a ratio of 1:1.33, and mixed evenly; then deionized water was added in batches, mixed and stirred evenly, and the conductive slurry (viscosity: 20-60mpa.s, solid content 8±2%) was prepared.
[0069] The conductive slurry was transferred and coated onto the copper foil by a gravure roller at a coating speed of 60 m / min. After being dried in an oven, the copper foil was rolled up to obtain a negative electrode current collector.
[0070] The present embodiment also provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode current collector is the negative electrode current collector of the present embodiment; the negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder, the negative electrode active material is a composition of graphite and silicon carbon (i.e., porous carbon and silicon carbon embedded in porous carbon), the conductive agent is conductive carbon black, and the binder is SBR+CMC (1:1.33), and the ratio between the substances in the negative electrode active material layer is graphite: silicon carbon: binder: conductive agent = 92.35:5:2.5:0.15.
[0071] Preparation process of negative electrode sheet: Graphite, silicon carbon, binder (SBR+CMC) and conductive agent are mixed in a mass ratio of 92.35:5:2.5:0.15, deionized water is added, and the mixture is fully stirred and mixed in a vacuum mixer to obtain negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and after drying at room temperature, it is transferred to an oven for drying, rolled up, and then rolled to obtain a negative electrode sheet. Among them, the coating surface density of the negative electrode slurry is 0.165g / 1540mm 2 ; The compaction after rolling is 1.65g / cc.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that the mass ratio of the conductive agent, the binder and the inorganic particles in the conductive layer is 60:36:4.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that the mass ratio of the conductive agent, the binder and the inorganic particles in the conductive layer is 55:36:9.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that the particle size D10 of boehmite is 0.8 μm, and D95 is 0.9 μm; and the size of the boehmite protruding from the conductive layer is 0.1 μm.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that the particle size D10 of boehmite is 0.95 μm, and D95 is 1.03 μm; and the size of the boehmite protruding from the conductive layer is 0.2 μm.
[0080] Example 6
[0081] The difference between this embodiment and embodiment 1 is that the conductive agent uses conductive graphite and carbon nanotubes, and the mass ratio of the conductive graphite to the carbon nanotubes is 3:1.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is that the conductive agent uses conductive graphite and carbon nanotubes, and the mass ratio of the conductive graphite to the carbon nanotubes is 4:1.
[0084] Example 8
[0085] The difference between this embodiment and embodiment 1 is that the conductive agent uses conductive graphite and carbon nanotubes, and the mass ratio of the conductive graphite to the carbon nanotubes is 5:1.
[0086] Example 9
[0087] The difference between this embodiment and embodiment 1 is that the conductive agent uses conductive graphite and carbon nanotubes, and the mass ratio of the conductive graphite to the carbon nanotubes is 6:1.
[0088] Example 10
[0089] The difference between this embodiment and embodiment 1 is that the conductive agent uses conductive graphite and carbon nanotubes, and the mass ratio of the conductive graphite to the carbon nanotubes is 2:1.
[0090] Embodiment 11
[0091] The difference between this embodiment and embodiment 6 is that boehmite is replaced by alumina.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 is that no boehmite is added, and the ratio of conductive graphite to binder is 60:40.
[0094] Comparative Example 2
[0095] The difference between this comparative example and Example 1 is that the mass ratio of the conductive agent, the binder and the inorganic particles in the conductive layer is 50:36:14.
[0096] Comparative Example 3
[0097] The difference between this comparative example and Example 4 is that the particle size D10 of the boehmite is 1.3 μm; D95 is 1.42 μm, and the size of the boehmite protruding from the surface of the conductive layer is 0.4 μm.
[0098] Comparative Example 4
[0099] The difference between this comparative example and Example 4 is that the particle size D10 of the boehmite is 0.6 μm; D95 is 0.71 μm, and the boehmite is embedded in the conductive layer and does not protrude from the surface of the conductive layer.
[0100] The negative electrode current collectors and negative electrode sheets prepared in the above Examples 1 to 11 and Comparative Examples 1 to 5 were subjected to performance tests respectively. The test results are shown in Table 1. The test methods are as follows:
[0101] 1) Test of the size of inorganic particles protruding from the surface of the conductive layer: The negative electrode current collectors of each embodiment and comparative example were cut into square samples of 10 mm × 10 mm, and then the samples were placed on the stage and aligned below the eyepiece of the white light interferometer. After focusing, scanning was started. After scanning, roughness analysis was performed based on the formed 3D image. The roughness is the size of the inorganic particles protruding from the surface of the conductive layer.
[0102] 2) Peeling test of conductive layer and plain foil (copper foil): A 15 mm wide 3M tape was pasted on the conductive layer of the negative electrode current collector, and a 2KG roller was used to roll back and forth 3 times (one round trip was considered as 1 time). Then, a peeling device was used to peel the film at a speed of 50 m / min, and the peeling force was recorded. Three data points were tested for each sample, and the average value was taken as the final result. The test results are shown in Table 1.
[0103] 3) Peeling force test of negative electrode active material layer (the negative electrode active material layer is peeled off from the negative electrode current collector, and the conductive layer is generally in one layer with the copper foil): 20MM×100MM rectangular peeling samples are cut from the negative electrode sheets of each embodiment and the comparative example at the same position, and the samples are subjected to peeling strength test using a Japanese IMADA peeling machine at a peeling speed of 100mm / min. The data of the stable section of the peeling force are intercepted, 3 data are tested for each sample, and the average value is taken as the final result. The test results are shown in Table 1.
[0104] 4) Electrode penetration resistance test: Cut 20MM×20MM square samples at the same position of the negative electrode sheets of each embodiment and the comparative example, and use Yuanneng Technology BER2500 electrode sheet resistance meter to measure the electrode sheet resistance. The pressure is 25MPa and the pressure is maintained for 15s. Each sample is tested for 6 data and the average value is taken as the final result. The test results are shown in Table 1.
[0105] Table 1: Parameters and performance tests of Examples 1 to 11 and Comparative Examples 1 to 4
[0106]
[0107]
[0108] Comparing Examples 1 to 3 and Comparative Examples 1 and 2, under the premise that the thickness of the conductive layer and the particle size of boehmite remain consistent, the content of boehmite affects the stripping force of the negative electrode active material layer and the penetration resistance of the pole piece. The test results of Table 1 show that as the content of boehmite increases, the stripping force between the conductive layer and the light foil and the stripping force between the negative electrode active material layer and the negative electrode current collector gradually increase, which shows that the addition of boehmite can effectively improve the roughness of the surface of the negative electrode current collector, increase the degree of mechanical engagement between the negative electrode active material layer and the negative electrode current collector, thereby reducing the slip during the rolling process and improving the stripping force of the negative electrode active material layer. But at the same time, the penetration resistance of the pole piece also increases with the increase of the boehmite content, and the increase of the penetration resistance of the pole piece will lead to an increase in the internal resistance of the battery, so that the energy loss of the battery during the charge and discharge process increases, and the output power and efficiency of the battery are reduced. Therefore, the amount of boehmite added needs to be controlled within a suitable range to improve the stripping force of the pole piece, and the increase in the penetration resistance of the pole piece will not be too large.
[0109] Comparing Example 1, Examples 4 and 5 and Comparative Examples 3 and 4, when the content of each component in the conductive layer and the thickness of the conductive layer remain consistent, the particle size of boehmite will affect the peeling force of the negative electrode active material layer. The test results in Table 1 show that as the particle size of boehmite increases, the size of the boehmite protruding from the conductive layer increases, and the roughness of the surface of the negative electrode current collector increases, thereby increasing the peeling force between the negative electrode active material and the negative electrode current collector. If the particle size of boehmite is too small, the boehmite will be embedded in the conductive layer and will not protrude from the surface of the conductive layer, and will not be able to play its role; if the particle size of boehmite is too large, the size of the boehmite protruding from the conductive layer is too large, affecting the overall size of the negative electrode current collector and the negative electrode sheet, and may also scratch the sheet.
[0110] Comparing Example 1 with Examples 6 to 10, the composition of the conductive agent in the conductive layer will also affect the stripping force and penetration resistance of the pole piece. Compared with Example 1, Examples 6 to 10 all use a combination of conductive graphite and carbon nanotubes. The test results in Table 1 show that the stripping force of the pole piece is improved and the penetration resistance of the pole piece is reduced by using a conductive agent compounded with conductive graphite and carbon nanotubes compared to a single conductive graphite. This shows that the use of large-particle conductive graphite and small-particle carbon nanotubes is helpful in constructing the void structure of the conductive layer. The rich pore structure makes the embedding effect of the negative electrode active material layer better, further improving the stripping force of the negative electrode active material layer, and at the same time increasing the contact area with the negative electrode active material and reducing the internal resistance. In addition, the conductivity of carbon nanotubes is better than that of conductive graphite. To improve the conductivity of the same level, the conductive graphite required is larger than that of carbon nanotubes. By adding carbon nanotubes to the conductive layer, the use of conductive graphite can be reduced. Therefore, as the amount of carbon nanotubes used increases, the penetration resistance of the pole piece gradually decreases.
[0111] Comparing Example 6 and Example 12, when other parameters remain the same, the type of inorganic particles mainly affects the peeling force of the negative electrode plate. Since the hardness of alumina is harder than that of boehmite, the degree of deformation during the rolling process of the plate is smaller, and it is easier to hinder interfacial slip, thereby improving the peeling force of the negative electrode active material layer.
[0112] The negative electrode current collector provided by the present invention is provided with a conductive layer in the current collector matrix. By introducing inorganic particles into the conductive layer, the roughness of the conductive layer surface can be increased, the degree of mechanical engagement between the negative electrode active material layer and the conductive layer can be increased, the slippage during rolling can be reduced, the stripping force of the negative electrode active material layer can be increased, and the risk of active material falling off during the negative electrode cycle can be reduced. In addition, the type of conductive agent in the conductive layer is adjusted, and large-particle graphite is compounded with a second conductive agent with small particles. While increasing the conductivity of the conductive layer, it is easier to build a pore structure, so that the embedding effect of the negative electrode active material layer is better, it is easier to hinder the interface slippage, further improve the stripping force of the negative electrode active material layer, and reduce the glue consumption. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0113] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode current collector, characterized in that: include: a current collector matrix; A conductive layer, disposed on the current collector substrate; Wherein, based on the total weight of the conductive layer being 100%, the conductive layer comprises the following components: 55-60% conductive agent, 35-37% binder and 3-10% inorganic particles; The inorganic particles partially protrude from the surface of the conductive layer, and the size of the inorganic particles protruding from the surface of the conductive layer is 0.1 μm to 0.2 μm.
2. The negative electrode current collector according to claim 1, characterized in that: The conductive agent includes a first conductive agent including conductive graphite.
3. The negative electrode current collector according to claim 2, characterized in that: The particle size D50 of the conductive graphite is 0.7 μm to 1 μm.
4. The negative electrode current collector according to claim 2, characterized in that: The conductive agent further includes a second conductive agent, and the second conductive agent includes one or more of Ketjen black, carbon nanotubes, graphene, and carbon fibers.
5. The negative electrode current collector according to claim 4, characterized in that: The mass ratio of the first conductive agent to the second conductive agent is (3-5):
1.
6. The negative electrode current collector according to claim 1, characterized in that: The single-side thickness of the conductive layer is 0.7 μm to 1 μm; and / or the particle size D10 of the inorganic particles is 0.8 μm to 1 μm, and D95 is 0.9 μm to 1.2 μm.
7. The negative electrode current collector according to claim 1, characterized in that: The inorganic particles include one or both of boehmite and alumina; and / or the binder is one or more of modified polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, and polymethyl methacrylate.
8. A negative electrode plate, characterized in that: The invention comprises the negative electrode current collector according to any one of claims 1 to 7 and a negative electrode active material layer located on the conductive layer of the negative electrode current collector.
9. The negative electrode sheet according to claim 8, characterized in that: The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as described in claim 8 or 9.
Citation Information
Patent Citations
Positive electrode for lithium secondary battery and method for preparing same
CN107565092A
Negative current collector, negative plate, lithium-ion secondary battery and preparation methods thereof
CN109390588A
Preparation method of negative carbon-coated current collector, negative pole piece containing negative carbon-coated current collector and application of negative pole piece
CN114843447A
Conductive coating composition for electrode sheet, electrode sheet, secondary battery, and electronic device
CN116111097A
Secondary battery and electric device
CN118782883A